Prevalence and Causes of Blindness: Results from Rapid Assessment of Avoidable Blindness (RAAB) survey in Gezira State, Sudan, 2010 - Hashim Binnawi, Kamal; Mohamed, Awad Hassan; Alshafae, Balgis Alkhair; Abdalla, Zainab; Alsanosi, Mazin; Ahmed, Mamoun Mirghani (مجلة الجزيرة للعلوم الصحية; مجلد 11 عدد 2 (2015), 2015)
Objectives: To estimate the prevalence of avoidable blindness in people aged 50 years and older in Gezira state, Sudan using Rapid Assessment for Avoidable Blindness (RAAB) methodology. Design: Cross-sectional population-based survey. Participants: Forty three clusters of 50 people aged 50 years or older were selected by probability proportionate to size sampling of clusters. Households within clusters were selected through compact segment sampling. A total of 2150 eligible persons were selected, of whom 2103 (97.8%) were examined. Methods: Participants underwent a comprehensive ophthalmic examination in their homes by specially trained ophthalmic teams, including measurement of visual acuity (VA) with a tumbling- E chart and the diagnosis of the principal cause of visual impairment. Results: The prevalence of bilateral blindness (presenting VA < 3/60) was 9.37% (95% confidence interval [CI], ±1.95), and prevalence of bilateral visual impairment (VA of <6/18-6/60) was 3.9% (95% CI, ±1.10) in the sample. Definite avoidable causes of blindness (i.e., cataract, refractive error, trachoma, and corneal scarring) were responsible for 74.6% of bilateral blindness. Cataract was the major cause of blindness (57.4%) followed by glaucoma (17.3%). Conclusions: The prevalence of blindness in people aged 50 years and older in Gezira state was slightly higher than expected. The main cause of blindness is cataract, followed by glaucoma. Three quarters of blindness is due to avoidable causes.